Chromosome integration of the Vitreoscilla hemoglobin gene (vgb) mediated by temperature‐sensitive plasmid enhances γ‐PGA production in Bacillus amyloliquefaciens. Issue 2 (15th April 2013) - Zhang, Wei; Xie, Hui; He, Yulian; Feng, Jun; Gao, Weixia; Gu, Yanyan; Wang, Shufang; Song, Cunjiang
Abstract Oxygen is a limiting factor in the production of γ‐PGA by the glutamic acid‐independent strain Bacillus amyloliquefaciens LL3 because of the high viscosity of the culture broth. The vgb gene encoding Vitreoscilla hemoglobin (VHb) was introduced into LL3 to overcome the low concentration of dissolved oxygen (DO). First, recombinant plasmid pWHV was constructed by cloning vgb into the Bacillus expression vector pWH1520 and transformed into LL3. Carbon monoxide difference spectral analysis confirmed the expression of VHb. The γ‐PGA yield of LL3 (pWHV) under the optimized fermentation conditions increased by 9.56%. To overcome the instability of pWH1520 and to establish stable expression of VHb, the engineered strain LL3‐PVK was constructed by homologous recombination between the integration vector pKSVPVK and the 16S rRNA gene of LL3. The temperature‐sensitive plasmid was used to perform the integration, which successfully circumvented the obstacle of the low transformation efficiency of B. amyloliquefaciens LL3. Bacillus amyloliquefaciens LL3‐PVK showed an increase of 30% in γ‐PGA production, while the biomass was increased by 7.9%. To our knowledge, this is the first report describing enhancement of γ‐PGA production in a glutamic acid‐independent strain as a result of vgb expression.